In vitro antioxidant and cytotoxic activity of Muscari neglectum growing in Turkey - TAŞKIN, TURGUT (MARMARA UNIV, FAC PHARMACY, 2018)
Muscari species have been used as antirheumatic, stomachic, diuretic, expectorant and anti verruca in folk medicine. The species have also been used as food for humans and animals in Turkey. In this study, the antioxidant and cytotoxic activities of different extracts obtained from Muscari neglectum were studied. The antioxidant capacities of the extracts were evaluated with DPPH free radical scavenging activity, metal chelating capacity and ABTS cation radical scavenging capacity assays. The cytotoxic potentials of the extracts were determined by MTT and LDH assays on HeLa-cells (human cancer cell line) and NRK-52E-cells (rat kidney cell line). The aqueous extracts from M. neglectum bulbs (IC50 : 2.83 +/- 0.54 mg/mL) and herba (IC 50 : 8.52 +/- 1.3 mg/mL) exhibited stronger DPPH free radical scavenging activity than other extracts, respectively. The ethanol extract from M. neglectum bulbs showed the highest ABTS (27.88 %) cation radical scavenging activity. According to the metal chelating activity test results, the aqueous extracts from M. neglectum herba and bulbs showed the strongest metal chelating activity (28.99% and 28.07%, respectively).
Keywords: Muscari neglectum; antioxidant activity; cytotoxic activity; Turkey; HYACINTHACEAE; ASPARAGACEAE; PLANTS; ASSAY